REVOLUȚIA DIGITALĂ ȘI TRANSFORMAREA EDUCAȚIEI (Journal for Freedom of Conscience (Jurnalul Libertății de Conștiință), 2024)
The Digital Revolution and the Transformation of Education.As the world becomes increasingly interconnected and dependent on  technology, adopting digital tools and methodologies in education is no  longer an option, but a necessity. Starting from these realities of the times we  live in, this article explores the role of digitization in modern education  and its far-reaching implications.